2018
DOI: 10.1126/sciadv.1701373
|View full text |Cite
|
Sign up to set email alerts
|

Atomically thin gallium layers from solid-melt exfoliation

Abstract: A unique way to synthesize innovative 2D gallenene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
192
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(198 citation statements)
references
References 85 publications
(90 reference statements)
4
192
2
Order By: Relevance
“…In 2018, Kochat et al ingeniously used the low melting point of gallium to produce gallenene with atomic thickness. They first formed gallium droplets by heating, then droplets are contacted briefly with Si/SiO 2 substrates at temperature of its melting point, and separated . Gallium on the substrate will form gallenene when it is cooled and solidified in liquid layer.…”
Section: Classification Of 2d Crystalsmentioning
confidence: 99%
“…In 2018, Kochat et al ingeniously used the low melting point of gallium to produce gallenene with atomic thickness. They first formed gallium droplets by heating, then droplets are contacted briefly with Si/SiO 2 substrates at temperature of its melting point, and separated . Gallium on the substrate will form gallenene when it is cooled and solidified in liquid layer.…”
Section: Classification Of 2d Crystalsmentioning
confidence: 99%
“…However, 2D materials with metallic bonding are largely unexplored. Some metals are known to form 2D structures on supports, including K on graphene [17][18][19], Pb and In on Si(111) [20], Hf on Ir(111) [21], Sn on Bi 2 Te 3 (111) [22], Rh on polyvinylpyrrolidone [23], and Ga on multiple substrates [24]. Compared to covalent 2D materials, metallic bonding prefers close-packed structures, not layered ones.…”
Section: Introductionmentioning
confidence: 99%
“…This was extended by Feng et al where the as‐grown β 12 borophene sheets on Ag (111) with rectangular unit cell showed a structural phase transition at 650K to the χ 3 ‐phase with in‐plane zig‐zag atomic arrangement . Among other group III elements, Kochat et al demonstrated exfoliation techniques to isolate atomically tin gallium, or gallenene, along the a and b crystallographic directions from melting droplet of bulk crystal near room temperature ( T m of Ga = 30 °C) . The exfoliated sheets displayed metallic conductivity and compatibility with a variety of substrates along with inducing a 2H‐1T structural phase transition when coupled as a heterostructure with monolayer MoS 2 .…”
Section: Synthesis Of Elemental 2d Materialsmentioning
confidence: 90%
“…Copyright 2017, American Physical Society. Images for “Buckled‐Ga” (Group III) and “Planar” (Group IV): Reproduced with permission . Copyright 2018, The Authors, published by American Association for the Advancement of Science (AAAS).…”
Section: Crystal Allotropes Of Elemental 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation